Electronic media : then, now and later - Medoff, Norman J.; Kaye, Barbara K. (Routledge, 2017)
Electronic Media: Then, Now, and Later provides a synopsis of the beginnings of electronic media in broadcasting and the subsequent advancements into digital media. The Then, Now, and Later approach focuses on how past innovations laid the groundwork for changing trends in technology, providing the opportunity and demand for evolution in both broadcasting and digital media. An updated companion website provides links to additional resources, chapter summaries, study guides and practice quizzes, instructor materials, and more. This new edition features two new chapters: one on social media, and one on choosing your entertainment and information experience. The then/now/later thematic structure of the book helps instructors draw parallels (and contracts) between media history and current events, which helps get students more engaged with the material. The book is known for its clear, concise, readable, and engaging writing style, which students and instructors alike appreciate. The companion website is updated and offers materials for instructors (an IM, PowerPoint slides, and test bank).